Senario the movie - Ahmad Puad Onah (Kuala Lumpur : Grand Brilliance [production company] ; Kuala Lumpur : Speedy Video [distributor])
Sebuah filem Melayu arahan Aziz M. Osman
Penerbit eksekutif, Lazizah Ahmad ; pengarah fotografi, Badaruddin Omar
Azlee Jaafar, Wahid Senario, Mazlan Pet Pet, Saiful Apek, Shamsul Ghau Ghau, Anne Hamid
Keywords: Motion pictures -- Malaysia; Malay drama; Comedy films